"What Deepest Remains": How Photojournalistic Mutualism between Robert Capa and Elmer W. Lower Shaped Modern Concepts of World War II. Issue 4 (1st October 2016) - Holiday, Steven; Cressman, Dale L.
Abstract : As American combat photographers documented the horrors and heroism of every major front of World War II, photo editors worked behind the scenes to bring their images to publication. Matching photographers with assignments and selecting images that best told the story—all while navigating censorship, publication expectations, and intercultural societal norms—the photo editor was indispensable to the combat photographer. The partnership of Robert Capa and Elmer W. Lower exemplified such a mutualistic relationship. Whether serendipitous, as it was early in the war when Lower provided assistance in exchange for Capa's photos, or calculated, as it was later in the war when both were employed by Life magazine, their experience exemplifies the mutually beneficial relationship of war photographers and their editors.